Ritual, sprog og verden - Jensen, Jeppe Sinding (Religionsvidenskabeligt Tidsskrift, 1992)
Reflektioner over et brud i ritualforskningen. Theories of ritual have mainly focused on the various functions of ritual. S shift in the study of ritual has occurred through two recent publications, i.e. Rules without Meaning by Frits Staal (1989) and Rethinking Religion by E. Thomas Lawson and Robert N. McCauley (1990). Both works draw on theoretical linguistics, in particular the transformational and generative grammars formulated by Noam Chomsky and attempt to apply this theorizing in pursuit of formal properties of ritual system. whereas Staal concentrates on the purely rule-governed, Lawson and McCauley include semanti dimeensions in their investigations of ritual syntax. this article cirtically surveys both works, their theses and divergences, and their validity and applicability in the history of religion.